2017
DOI: 10.1186/s12929-016-0308-6
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant methylation of DACT1 and DACT2 are associated with tumor progression and poor prognosis in esophageal squamous cell carcinoma

Abstract: BackgroundThe DACT (Dishevelled-associated antagonist of β-catenin) family of scaffold proteins may play important roles in tumorigenesis. However, the epigenetic changes of DACT1, 2, 3 and their effect on esophageal squamous cell carcinoma (ESCC) have not been investigated so far. The aim of this study was to investigate the promoter methylation and expression of DACT family, in order to elucidate more information on the role of DACT with regard to the progression and prognosis of ESCC.MethodsMSP and BGS meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 35 publications
2
18
0
3
Order By: Relevance
“…The reactivated DACT1 gene inhibited the invasion and metastasis of NPC cells. Guo et al [14] have found that abnormal methylation of the DACT1 gene was associated with the progress and poor prognosis of esophageal squamous cell carcinoma. Deng et al [15] found that the number of methylation sites in the CpG island of the DACT1 gene was related to the prognosis of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The reactivated DACT1 gene inhibited the invasion and metastasis of NPC cells. Guo et al [14] have found that abnormal methylation of the DACT1 gene was associated with the progress and poor prognosis of esophageal squamous cell carcinoma. Deng et al [15] found that the number of methylation sites in the CpG island of the DACT1 gene was related to the prognosis of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The genes corresponding to the five methylation sites (cg05008070, cg07227049, cg13759702, cg16376000, and cg23170347) were DACT1, VRK2, MELTF, FGF12, and PRICKLE2, which were all protein coding genes. DACT1, VRK2, MELTF, and FGF12 have been implicated in cancers other than CC (Dmitriev et al, 2015;Fernandez et al, 2010;Guo et al, 2017), and PRICKLE2 has been reported to correlate with CC (Senchenko et al, 2013). Future studies will be required to elucidate the functional impact of aberrant methylation of these five genes in CC development.…”
Section: Risk Stratificationmentioning
confidence: 99%
“…DNA methylation is usually considered as a silencing epigenetic marker in diseases like cancer [12]. For example, the methylation of Dishevelled Binding Antagonist of Beta Catenin (DACT) 1and DACT 2 was associated with the development of esophageal squamous cell carcinoma (ESCC) and was regarded as prognostic biomarkers of ESCC [13]. Methylation of DNA repair gene O-6-methylguanine-DNA methyltransferase (MGMT) promoter region has been correlated with better prognosis of glioblastoma multiforme [14].…”
Section: Introductionmentioning
confidence: 99%